Day 2 Tue, September 15, 2015 2015
DOI: 10.2118/175832-ms
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Reaction Kinetics and Diffusion Rate of Dolomitic Rock with HCl

Abstract: Diffusion coefficient (De) is an important parameter used in both matrix acidizing and acid fracturing job design. There are two major limitations of conventional lab practices. Firstly, De is obtained at 1000 psi (or below) system pressure, which is too low to represent realistic reservoir conditions. Secondly, De obtained from conventional lab practice is based on fresh acid, which largely ignores the impact of reaction products, especially CO 2 .Herein, we investigate the effects of both pressure and reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition to the reaction rate, the diffusion coefficient, activation energy, reaction order, and the reaction regimes can be predicted from RDA experiments . RDA was used in determining the rate of calcite and dolomite dissolution using emulsified acids , and HCl. Also, the kinetics of formulation composed of gelled acids , and organic acids , with reservoir rock has been studied. The kinetics of pyrite present in Bazhenov shale has also been studied .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the reaction rate, the diffusion coefficient, activation energy, reaction order, and the reaction regimes can be predicted from RDA experiments . RDA was used in determining the rate of calcite and dolomite dissolution using emulsified acids , and HCl. Also, the kinetics of formulation composed of gelled acids , and organic acids , with reservoir rock has been studied. The kinetics of pyrite present in Bazhenov shale has also been studied .…”
Section: Introductionmentioning
confidence: 99%
“…Khalid et al 81 conducted research on the kinetics and diffusion rate of HCl reacting with dolomite, using an RDA at a high pressure and constant temperature of 150 °F. Four different concentrations of HCl were used in the experiment, one fresh and three spent acids.…”
Section: Annular Flow Reactormentioning
confidence: 99%
“…Khalid et al 81 suggested that when fresh HCl reacts with dolomite, the pressure at which the experiment (using RDA) is conducted affects the rate of reaction and the diffusion coefficient. The results of their Silurian dolomite experiment indicated that the diffusion coefficient was about 23% overestimated when using a lower system pressure, as compared to when using a higher pressure (high enough for the CO 2 to remain soluble).…”
Section: Annular Flow Reactormentioning
confidence: 99%